Conservation of Memory Heritage through the artwork “Sea Present” painted by Shigeru AOKI - Cheong, Ilji (International Planning History Society Proceedings, 2018)
The scope of cultural heritage is beginning to extend to the modern ear and holistically covers buildings and lifestyle. Using memory has become to be applied as one of the methods for conservation while it is usually used in short duration or just for one heritage. It is hardly ever extended to urban planning. In this paper, I proposed the memory project in Mera village and considered the collaboration among five sectors through three memories. The memory project became virtuous circle to produce community initiatives and new memories at the same time. And, I determined memory heritages through the changes of the relationship between the memories and the spaces. There was a possibility for memory urbanism too. Finally, I revealed the interaction and mediation among five sectors for the conservation of the museum of “Sea Present”. It said that the importance of realistic and balanced viewpoints with authenticity.